2014
DOI: 10.1016/j.polymertesting.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, viscoelastic and mechanical behavior of polypropylene with synthetic boehmite alumina nanoparticles

Abstract: Effects of nanofiller concentration and surface treatments on the morphology, thermal, viscoelastic and mechanical behaviors of polypropylene copolymer (PP)/boehmite alumina (BA) nanocomposites were investigated. Both untreated and treated BA particles with octylsilane (OS) and with sulphonic acid compound (OS2) were added up to 10 wt% to produce nanocomposites by melt mixing followed by film blow molding and hot pressing. Dispersion of BA was studied by scanning electron microscopy. Differential scanning calo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 39 publications
4
24
0
4
Order By: Relevance
“…Meanwhile, Figure (a) shows that the fractured surface after hand breaking of 2 wt % AlOOH nanocomposites has a big hole, which is not observed in the fractured surface after tensile test [Figure (b)]. The enhanced ductility can be explained by a failure mode in which particle debonding with massive voiding occurs first, followed by void coalescence associated with matrix fibrillation …”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, Figure (a) shows that the fractured surface after hand breaking of 2 wt % AlOOH nanocomposites has a big hole, which is not observed in the fractured surface after tensile test [Figure (b)]. The enhanced ductility can be explained by a failure mode in which particle debonding with massive voiding occurs first, followed by void coalescence associated with matrix fibrillation …”
Section: Resultsmentioning
confidence: 99%
“…In addition to its good dispersibility, BA is a low‐cost filler that is easy to produce. BA particles range in the tens of nanometer (nm) in size and can be organically modified to enhance their interactions with polymer chains and permit their use with a wide range of polymers …”
Section: Introductionmentioning
confidence: 99%
“…reported that the incorporation of BA particles enhanced the stiffness and strength of PS. BA particles were also added to a PP matrix by Pedrazzoli et al . and their results indicate that the tensile modulus of the PP was improved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with previous studies, the pure CS showed characteristic bands at 2θs of 23 and 19°. The characteristic peaks at 2θs of 38 and 49° were attributed to the orthorhombic crystalline form of the boehmite nanofillers . The incorporation of boehmite nanofillers resulted in a reduction or even the disappearance of the characteristic peak at a 2θ of 23°; this was mainly due to the interference of nanofillers with orderly packed CS chains through interfacial interactions and, hence, the reduction of the crystalline domain of the polymer.…”
Section: Resultsmentioning
confidence: 96%